Liquid-Liquid Extraction and Spectrophotometric Determination of Ni (II) using 5-nitrosalicylaldehyde semicarbazone (NSS) as an Analytical Reagent - Ram L.S.; Kalpana P.J.N.; Irfan M.R. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
5-nitrosalicylaldehyde semicarbazone (NSS) is proposed as a new sensitive reagent for the sensitive extractive spectrophotometric determination of Ni (II). NSS reacts with Ni (II) in the pH range 4.0 to 4.4 to form a coloured complex, which was well extracted into Ethyl acetate. The absorption spectrum of Ni (II) NSS complex in Ethyl acetate shows maximum absorbance at 420 nm. It was observed that the colour development was instantaneous and stable for 48 hrs. The system obeyed Beer’s law up to 1-6 µg / cm3. The molar absorptivity calculated was found to be 2.5016 * 104 lit mol-1 cm-1 and the sensitivity of the method as defined by sandal’s was 1.067 * 10-2 μg/cm2 . The composition of the extracted species was determined by Job’s Continuous variation method and Mole ratio method was found to be 1:4. It may be satisfactorily applied for the determination of Ni (II) with present method.